Tradisi Bapalas Bidan dalam Budaya Lokal antara Ungkapan Syukur dan Tantangan Profesionalime Kebidanan - Ika Mardiatul Ulfa; Aisyah Aisyah; Elvi Elvi; Kiki Andriani; Novia Karolina; Chesi Yolania; Devia Lestari; Eliska Kornelia; Fridolce Bahan; Gea Gea (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
The Bapalas Bidan tradition is a ritual of the Dayak tribe in Kalimantan to express gratitude to the midwife after the birth process. The ritual includes activities such as bathing the baby, serving offerings, and performing a symbolic ceremony to spiritually "return" the baby from the midwife to its parents. In the past, these rituals had a magical element, but nowadays more prayers and Islamic principles are applied. While modern midwifery practice faces challenges to its survival, this tradition remains crucial as it strengthens culture and social connections. This study examines the meaning of the tradition, its evolution, and the ways in which communities maintain it in modern times.